Needs Analysis of English for Specific Purposes Among Mining Engineering Students at Halu Oleo University - Wa Ode Fatima Azzahra; Yazid Yazid; La Ode Nggawu (Halu Oleo University, 2023)
Teaching English to Mining Engineering students is divided into General English (GE) and English for Specific Purposes (ESP), with GE covering general skills and ESP focusing on scientific English. This research aims to identify the English learning needs of students in the Mining Engineering Department at Halu Oleo University. Using a survey method, data were collected through questionnaires and interviews from 60 respondents, including students, a lecturer, and graduates. The data were analyzed using SPSS. The findings indicate that students' primary needs for learning English are exam preparation, career advancement, completing studies, self-improvement, further education, and international travel. Students need to improve their vocabulary, listening, grammar, speaking, pronunciation, reading, and writing. Important mining topics include dilution, mining engineering, and disposal. Students face challenges such as lack of learning strategies, difficulty understanding texts, writing issues, low motivation, and limited vocabulary. Preferred learning methods include reading, audio materials, films, pair work, visual aids, individual study, and speaking while listening.